2023
DOI: 10.1038/s41467-023-39758-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional images reveal the impact of the endosymbiont Midichloria mitochondrii on the host mitochondria

Abstract: The hard tick, Ixodes ricinus, a main Lyme disease vector, harbors an intracellular bacterial endosymbiont. Midichloria mitochondrii is maternally inherited and resides in the mitochondria of I. ricinus oocytes, but the consequences of this endosymbiosis are not well understood. Here, we provide 3D images of wild-type and aposymbiotic I. ricinus oocytes generated with focused ion beam-scanning electron microscopy. Quantitative image analyses of endosymbionts and oocyte mitochondria at different maturation stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Additionally, it was also detected in D. marginatus, in agreement with a previous study [68]. A recent report showed that this mitochondrial-residing bacterium affects oogenesis [69], but much remains to be known regarding the impact of its presence in ticks. Although this bacterium can be transmitted through tick bites [64], another study showed no clinical signs in people exclusively infected with M. mitochondrii; however, although it may not be harmful to humans, it could play a role in TBP transmission to mammalian hosts [62], since endosymbionts like M. mitochondrii often maintain a delicate microbial balance in ticks, hindering the presence of other microbes, blocking related pathogens or even enhancing their presence.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, it was also detected in D. marginatus, in agreement with a previous study [68]. A recent report showed that this mitochondrial-residing bacterium affects oogenesis [69], but much remains to be known regarding the impact of its presence in ticks. Although this bacterium can be transmitted through tick bites [64], another study showed no clinical signs in people exclusively infected with M. mitochondrii; however, although it may not be harmful to humans, it could play a role in TBP transmission to mammalian hosts [62], since endosymbionts like M. mitochondrii often maintain a delicate microbial balance in ticks, hindering the presence of other microbes, blocking related pathogens or even enhancing their presence.…”
Section: Discussionsupporting
confidence: 91%
“…Davide Sassera (University of Pavia, Italy) described advances in research on Midichloria , a genus of tick-borne mutualist bacteria, found to reside within the intermembrane space of different tick species (Stavru et al 2020 ). Advanced 2D and 3D electron microscopy suggested that Midichloria bacteria influence mitochondrial network fragmentation (Uzum et al 2023 ). Additionally, comparative genomics revealed a possible connection between the bacterium’s ability to colonize mitochondria and the presence of specific genetic traits, including type IV secretion system and flagellum (Floriano et al 2023 ).…”
Section: Scientific Programmementioning
confidence: 99%